Prevalence and Attitudes Towards Using Protein Supplements Among Female Gym Users: An Online Survey - Alhussain, Maha H.; Abdulhalim, Waad S.; Al-harbi, Laila N.; Binobead, Manal Abdulaziz (Current Nutrition & Food Science, 2022)
Background: Protein supplements have become a widespread practice amongst athletes and gym users worldwide. However, studies on the use of protein supplements among female gym users in Saudi Arabia are lacking. Objective: The aim of this study was to investigate the prevalence of protein supplement usage among female gym users and their attitudes towards protein supplementation in Riyadh city, Saudi Arabia. Methods: In this cross-sectional study, 502 female gym users aged ≥18 years completed a structured, self-administered online questionnaire on the usage of protein supplementation. Socio- demographic information, anthropometry, health status, exercise frequency, attitudes and knowledge regarding protein supplements were obtained. Results: The overall prevalence rate of protein supplement use among the study respondents was 36.3%. There were significant associations between the use of protein supplements and educational level (p< 0.05), the duration of being a gym member (p< 0.05) and frequency of gym visits per week (p< 0.05). Whey protein was the predominantly used supplement (57.8%), and the reason attributed to the use of protein supplement was muscle building (53.9%). The main sources of information regarding protein supplement use included the internet (30.2%) followed by gym coaches (25.3%). Conclusion: Our findings demonstrated that a considerable number of females exercising in gyms use protein supplements, and most rely on unreliable sources for decision-making of protein supplements use. Nutritional education and consultations regarding protein supplement use are warranted.
Keywords: prevalence